2023
DOI: 10.9734/ajee/2023/v20i4445
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Plant Species in Ghana: Route of Spread, Socio-Economic and Environmental Impact

Abstract: Globally, there has been a rapid increase in biodiversity loss, these losses have been attributed to habitat loss and invasive flora and fauna species. Extensive work has been done on the losses brought about by invasive fauna species, however, the impact of invasive flora species has less been explored in Ghana. This review focused on the various alien plant species found in Ghana and the factors that support their spread, establishment, and colonization. Findings indicate that the common invasive plants in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Menalled et al [27] also reported that agricultural practices affect the abundance of and variation in weeds in the long term. In some cases, invasive weeds proliferate, becoming dominant and affecting the ecosystem [28,29]. Ismail et al [30] illustrated that although the CI regime was put in place to suppress the growth of weeds, these weeds also adapted to flooding owing to the evolution of flood tolerance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Menalled et al [27] also reported that agricultural practices affect the abundance of and variation in weeds in the long term. In some cases, invasive weeds proliferate, becoming dominant and affecting the ecosystem [28,29]. Ismail et al [30] illustrated that although the CI regime was put in place to suppress the growth of weeds, these weeds also adapted to flooding owing to the evolution of flood tolerance genes.…”
Section: Discussionmentioning
confidence: 99%